Lifestyle and Social Media Marketing as Drivers of Electronic Word of Mouth and Their Impact on Generation Z’s Online Batik Purchase Decisions - Falahy Mohamad; Farida Indriani (Yayasan Riset dan Pengembangan Intelektual, 2025)
Changes in the digital lifestyle of younger generations and the growing intensity of social media use have significantly transformed consumption patterns, including the online purchase of cultural products such as batik. Although batik has gained increasing visibility in digital spaces, the level of participation of Generation Z in online batik purchasing remains relatively limited. This study aims to examine the influence of lifestyle and social media marketing on positive electronic word of mouth (e-WOM) and their impact on online batik purchase decisions among Generation Z. The study employed a quantitative research approach, with batik consumers in Indonesia as the population. Samples were selected using purposive sampling criteria, including individuals aged 17–25 years who had previously purchased batik online and were familiar with the Berkain Bersama Movement. Data were collected through structured questionnaires and analyzed using the SEM–SmartPLS approach. The findings indicate that lifestyle and social media marketing positively influence positive e-WOM as well as online batik purchase decisions. Furthermore, positive e-WOM emerges as the most influential factor in shaping purchase decisions and plays a mediating role in the relationship between lifestyle, social media marketing, and purchasing decisions. These results highlight the strategic importance of integrating digital lifestyle alignment, effective social media marketing, and positive e-WOM to enhance Generation Z’s engagement and purchasing interest in cultural products within the digital marketplace.